Способ выделения оксидов редкоземельных элементов из шлифотходов от производства постоянных магнитов - Андреев А. А. Артем Андреевич; Буйновский А. С. Александр Сергеевич; Дьяченко А. Н. Александр Николаевич; Крайденко Р. И. Роман Иванович
опубл. 10.10.09